Kepastian Hukum Kewenangan Diskresi Direksi BUMN dalam Perspektif Prinsip Good Corporate Governance - Herwibowo, Bambang Hajar; Maryano, Maryano; Mau, Hedwig A. (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
This study examines the legal certainty of the discretionary authority of Directors of State-Owned Enterprises (SOEs) from the perspective of the principles of Good Corporate Governance (GCG). The issue arises when discretionary powers, which are intended to serve the business interests of the company, result in losses that are deemed state financial losses, thereby creating the potential for the criminalization of business decisions. This phenomenon reflects legal uncertainty and the suboptimal application of GCG principles as guidelines in strategic decision-making by SOE directors. The research employs a normative juridical method with a statute approach and a conceptual approach. Data sources include primary, secondary, and tertiary legal materials, analyzed deductively. The analysis focuses on the regulation of SOE directors’ discretionary authority based on Law Number 40 of 2007 concerning Limited Liability Companies, Law Number 19 of 2003 concerning State-Owned Enterprises and its amendments, as well as other relevant regulations, using the principles of transparency, accountability, responsibility, independence, and fairness as benchmarks. The findings reveal that, normatively, the discretionary authority of directors has a clear legal basis, but its implementation still faces obstacles such as regulatory overlap, differing interpretations by law enforcement authorities, and the absence of clear technical guidelines to distinguish between reasonable business losses and unlawful acts. Consistent enforcement of GCG principles can prevent the abuse of authority and protect directors from the risk of criminalization, provided that decisions are made in good faith, with due care, and free from conflicts of interest. Therefore, harmonization of regulations, strengthening of operational guidelines, and the establishment of an effective oversight system are required to ensure that SOE directors’ discretion can be exercised in an accountable manner while remaining adaptive to business dynamics.